2021
DOI: 10.1038/s41377-021-00505-w
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic semiconductor nanogroove array enhanced broad spectral band millimetre and terahertz wave detection

Abstract: High-performance uncooled millimetre and terahertz wave detectors are required as a building block for a wide range of applications. The state-of-the-art technologies, however, are plagued by low sensitivity, narrow spectral bandwidth, and complicated architecture. Here, we report semiconductor surface plasmon enhanced high-performance broadband millimetre and terahertz wave detectors which are based on nanogroove InSb array epitaxially grown on GaAs substrate for room temperature operation. By making a nanogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 70 publications
1
23
0
Order By: Relevance
“…In addition, the photocurrent was recorded with the modulation frequency f from 150 Hz to 100 kHz at 0.172 THz. The detector demonstrated a 3 dB bandwidth of 3.4 × 10 4 Hz, corresponding to a response time of 4.68 μs according to 𝜏 = 1 2𝜋f −3 dB , [5] which is consistent with the measurement result of the pulse in Figure 3f. We recorded the waveforms of the detector at 5 and 10 kHz in Figure 4f.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, the photocurrent was recorded with the modulation frequency f from 150 Hz to 100 kHz at 0.172 THz. The detector demonstrated a 3 dB bandwidth of 3.4 × 10 4 Hz, corresponding to a response time of 4.68 μs according to 𝜏 = 1 2𝜋f −3 dB , [5] which is consistent with the measurement result of the pulse in Figure 3f. We recorded the waveforms of the detector at 5 and 10 kHz in Figure 4f.…”
Section: Resultssupporting
confidence: 87%
“…However, it was observed that under the THz and MMW radiation, the resistance of the detector increases, which is the opposite of the result caused by the thermal effect. In addition, the thermal response speed is relatively slow, generally on the order of ≈ms, [ 5 ] which is much longer than the response time (≈2.5 µs) of the detector in THz and MMW bands. As a consequence, the contribution from the thermal effect can be excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the voltage of 25 V, the NEP of the QD microwheel array and QD film are 1.88 × 10 –14 and 6.6 × 10 –13 W Hz –1/2 , respectively. The rather lower NEP is just 1/7000 than a commercial Golay cell (140 pW Hz –1/2 ) and could be compared with the best results (2 × 10 –14 W Hz –1/2 ) obtained by the InSb nano grooves devices based on the same mechanism to our knowledge . The D * reaches 1.6 × 10 11 m Hz 1/2 W –1 which is 3 orders than the commercial thermal-type detector (1.9 × 10 8 m Hz 1/2 W –1 ) .…”
Section: Resultsmentioning
confidence: 50%
“…Bolometers, pyroelectrics, and thermopiles are among the most used thermal detectors. Some notable methods to improve the moderate responsivity of thermal detectors are the membrane-suspended bolometer structure to reduce thermal conduction [ 12 , 13 , 14 , 15 ], a novel THz antenna-coupled bolometer to optimize THz wave collection [ 16 , 17 ], an optical focusing lens [ 18 , 19 ], a metal grating absorber structure [ 20 , 21 , 22 ], and utilization of a highly sensitive thin film material [ 23 , 24 ]. Further performance enhancement is still widely possible by enabling state-of-the-art fabrication and measurement technologies.…”
Section: Introductionmentioning
confidence: 99%